Usia Ibu Hamil Dengan Kadar Hemoglobin Saat Abortus - Tristiana Yuniarti Sri Marwani; Asmar Yetti Zein; Hesty Widyasih (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: One of the major causes of maternal mortality in SDKI 2007 was postpartum bleeding, the number was 28% causes by anemia and chronic energy deficiency in pregnant women as the main cause of bleeding and infection. Anemia in pregnant women is signed by a decrease of haemoglobin levels especially in the high-risk age groups such as <20 and > 35 years old. Incidence of abortion in TemanggungHospital since 2008 - 2011 increased from 10% to 21%.Objective: To determine the relationship between the mother’s age and haemoglobin levels during abortion at the TemanggungHospital in 2011.Methods: Analytic observational cross-sectional design. The population in this study were all pregnant women that abortion in the TemanggungHospital in 2011 is 175 samples. The sampling technique used in this study was purposive sampling. The independent variables in this study was mother’s age and the dependent variable was haemoglobin level during abortion. Data analysis using Pearson product moment correlation test with a confidence level of 95% or α = 0.05.Results: The majority of pregnant women who have abortus aged 20-35 years by 65.14% and the highest haemoglobin levels at the time of abortion Hb ≥ 11 g% normal category at 56.58%. Value = ─ 0237 rcount greater than rtable = 0148 while the p-value = 0.0015Conclusion: There is a significant relationship between mother’s age and haemoglobin levels, the result shows negative relationship, and the value of closeness is low.Keywords: Mother’s age, haemoglobin level, abortion.